APAKAH PERTUMBUHAN PERUSAHAAN MEMODERASI PRAKTIK KEBERLANJUTAN, KEPEMILIKAN INSTITUSIONAL, DAN KESULITAN KEUANGAN AKIBAT PENGHINDARAN PAJAK PERUSAHAAN? - Putri Anasyah, Abela; Solikhah, Badingatus (Universitas Riau, 2026)
Corporate Tax Avoidance (CTA) remains a critical issue in developing countries such as Indonesia, where fiscal capacity heavily depends on corporate tax compliance. Prior studies examining the roles of CSR Disclosure (CSRD), Institutional Ownership (IOW), and Financial Distress (FD) on CTA report inconsistent findings and are predominantly limited to specific industries. Addressing this gap, this study investigates the relationships between CSRD, IOW, and FD on CTA, while incorporating Firm Growth (FG) as a moderating variable within a comprehensive cross-industry framework. Using secondary data from Refinitiv, this study analyzes 4,066 firm-year observations of all non-financial firms listed on the IDX 2020-2024. FEM regression is employed. The findings reveal that CSRD and FD are significantly positively associated with higher CTA, whereas IOW significantly constrains CTA. FG as a moderator significantly weakens the positive relationship of FD-CTA, but does not moderate CSRD or IOW effects. Robustness tests confirm result stability. Using a large cross-industry sample in a developing country, this study reduces sectoral bias in prior research. This study contributes it extends agency theory by showing that firm growth conditions distress-driven CTA.